Higher Order Thinking Skill (Hots) Ability Instrument for Theme 2 (Unity in Diversity) in Class VI Elementary School - Sri Mahalia Br Ginting; Desak Putu Parmiti (MIMBAR PGSD Undiksha, 2023)
The lack of focus on HOTS assessment in the education system can lead to a lack of encouragement for students to develop critical, analytical and creative thinking skills. This research aims to develop a HOTS instrument for HOTS abilities for sixth grade elementary school students with theme 2 (Unity in Difference). The development of instruments in this research was guided by the Borg and Gall model. The HOTS instrument developed is a test in essay form. Meanwhile, the object in this research is the quality of the question items. The data collected in this research is data regarding the HOTS ability instrument. The method used to collect data in this research is the test method. Data were analyzed using content validity analysis tests, item validity tests, reliability tests, discrimination tests, and difficulty level tests. The content validity test results tested by five HOTS Instrument experts were declared relevant, the average content validity test results were declared valid, the average instrument validity test results were declared valid, the average instrument reliability test results were at very high criteria, the average results of the power test results which are in the good different power criteria, the average results of the difficulty level scores of the questions which are in the medium level category of difficulty. It was concluded that the HOTS ability instrument for sixth grade elementary school students with theme 2 (Unity in Difference) is suitable for measuring students' HOTS abilities in solving problems and training students to think creatively.